Unified communications forensics : anatomy of common UC attacks - Grant, Nicholas, 1978- (Syngress is an imprint of Elsevier, 2013)
"Communication is a key part of our every day lives. Today, we communicate in ways that were not possible for the average consumer just 15 years ago. Currently, there are multiple mediums by which communication can take place, from telephony to email to instant messaging to video conferencing. Since the first call was made on the telephone in 1876, improvements have been made on the utilization and transport of the human voice from one location to another. However, to provide lower costs and enhanced features, VoIP has been on most everyone's radar. However, as the voice and data networks continue to converge there is a serious need to understand the technology and attack vectors and mean to protect company sensitive information within this bleeding edge technology"--